Cytostatic and antiviral 6-arylpurine ribonucleosides. Part 7: synthesis and evaluation of 6-substituted purine l-ribonucleosides - Hocek, Michal; Silhár, Peter; Shih, I-hung; Mabery, Eric; Mackman, Richard (Bioorganic & medicinal chemistry letters, 2006)
A series of purine l-ribonucleosides 2a-2i bearing diverse C-substituents (alkyl, aryl, hetaryl or hydroxymethyl) in the position 6 were prepared by Pd-catalyzed cross-coupling reactions of 6-chloro-9-(2,3,5-tri-O-acetyl-beta-l-ribofuranosyl)purine with the corresponding organometallics followed by deprotection. Unlike their d-ribonucleoside enantiomers that possess strong cytostatic and anti-HCV activity, the l-ribonucleosides were inactive except for 6-benzylpurine nucleoside 2h showing moderate anti-HCV effect in replicon assay. A triphosphate of 2h did not inhibit HCV RNA polymerase.
Keywords: molekulární struktura; Animals; vztahy mezi strukturou a aktivitou; HL-60 Cells; Humans; nádorové buněčné linie; protinádorové látky; Purine Nucleosides; In Vitro Techniques; mikrobiální testy citlivosti; lidé; Antiviral Agents; zvířata; proliferace buněk; purinové nukleosidy; antivirové látky; myši; Antineoplastic Agents; Drug Screening Assays, Antitumor; Ribonucleosides; techniky in vitro; screeningové testy protinádorových léčiv; HeLa Cells; ribonukleosidy; HL-60 buňky; Molecular Structure; Structure-Activity Relationship; Hepacivirus; Mice; Microbial Sensitivity Tests; Cell Proliferation; HeLa buňky; Cell Line, Tumor